Design And Construction Of A Website-Based Employee Work Results Monitoring System - Bima Triadmaja (Asosiasi Dosen Muda Indonesia, 2025)
Dwi Putra Tile Craftsman (PG. Dwi Putra) is a manufacturing industry in Klaten, Central Java, which produces three types of press tiles, namely mantili tiles, ordinary tiles, and kerpus. Recording the results of employees' work today is carried out manually, which often leads to inaccuracies in the data and hinders the calculation of salaries. Solving this problem requires a website-based employee monitoring system that can record, monitor, and report work results in real-time, and speed up salary calculations. This system aims to efficiently record employee work results, monitor productivity in real-time, provide accurate and structured work reports, automate the salary calculation process, and provide integrated and easily accessible data access. This system is built by using the Laravel Framework by implementing a Waterfall approach, and MySQL as a database. System testing is carried out with a Black Box approach and System Usability Scale (SUS). The results of the application of the Black Box method indicate that all system functions operate according to the expectations set by the researcher, resulting in a validity rate of 100%. The trial with SUS resulted in a grade of 82.5, which indicates that the system is functioning very well and has met the eligibility criteria.